FREQUENCY OF CD44 EXPRESSION IN DIAGNOSED CASES OF ORAL EPITHELIAL DYSPLASIA AND SQUAMOUS CELL CARCINOMA - Momin, Zumrud; Rahat, Noshaba; Shahzad, Humera; Umair, Marvi; Raima Kaleemi,; Khursheed, Asma (Journal of Ayub Medical College Abbottabad, 2024)
Background: Oral cavity cancer is one of the most widespread head and neck cancers in the world. 90 percent of oral cavity cancers are squamous cell carcinoma (SCC). Oral Potentially Malignant Disorder (OPMD), are well known to develop into squamous cell carcinoma. CD44 is a glycoprotein present on the cell surface and plays a vital role in cancer cell invasion, migration, metastasis of cancers and prognosis. The present study aims to detect the frequency of CD44 immunomarker expression in epithelial dysplasia and squamous cell carcinoma samples and correlates the expression with histologic grades of this lesion. Methods: cross sectional study at the Department of Pathology, BMSI, JPMC, Karachi between 01-01-2018 to 31-12-2021. 95 patients diagnosed on morphological characterization of the lesion as squamous cell carcinoma/dysplasia were selected by using non-probability purposive sampling technique, among them 41 were diagnosed as epithelial dysplasia and 54 as SCC and were subjected to immunohistochemistry. Results: A total of 95 cases were selected. The mean age was 49.32 years. The majority of cases were seen in 4th and 5th decades. 69 (72.6%) were males and 26 (27.4%) were females with male to female ratio 2.65:1. The closest site was buccal mucosa 75(78.9%). Among 41 cases of dysplasia, 36 showed membranous positivity for CD44 (87.8%), and 45 showed positive membranous CD44 immunoreactivity (83.3%) among 54 cases of squamous cell carcinoma. Conclusion: Increased frequency of CD44 expression was found with increasing grades of dysplasia and squamous cell carcinoma, which may be a possible indicator of malignant transformation and can serve as a prognostic biomarker for oral SCC.